Pathomorphological feature of chronic pancreatitis (CP) is the development of pancreatic fibrosis with the accumulation of various collagen types, tubulin, fibronectin, laminin, and also intermediate filament proteins produced by activated pancreatic stel - T.V. Turovskaya; A.M. Gnilorybov; L.V. Vasilyeva; V.B. Kostogryz; M.S. Goncharuk (Patologìâ)
Pathomorphological feature of chronic pancreatitis (CP) is the development of pancreatic fibrosis with the accumulation of various collagen types, tubulin, fibronectin, laminin, and also intermediate filament proteins produced by activated pancreatic stellate cells (PSCs), which express the cytoskeletal α-smooth muscle actin (α-SMA).